Backward Feature Elimination for Accurate Pathogen Recognition Using Portable Electronic Nose - Mukunthan, T.; Topal, C.; Fernando, A.; Ragione, R.L. (IEEE, 2020)
This paper presents the application of the backward feature elimination technique on an electronic nose (E-nose) to aid the rapid detection of pathogens using Volatile Organic Compounds (VOCs). The timely identification of pathogens is vital to facilitate control of diseases. E-noses are widely used for the identification of VOCs as a non-invasive tool. However, the identification of VOC signatures associated with microbial pathogens using E-nose is currently inefficient for the timely identification of pathogens. Therefore, we proposed an E-nose system integrating the backward feature elimination. Comprehensive experiments of backward feature elimination showed that they improve the classification accuracy.
Keywords: Electronic nose; Pathogen detection; Backward feature elimination